POLA PENGASUHAN ANAK DALAM KONTEKS PENDIDIKAN PERAN PEMERINTAH DAN ORANG TUA: Children's Care Patterns in Educational Context; Role of Government and Parents - Dicki Hartanto; Sri yuliani (UIR Press, 2019)
This study would like to reveal the magnitude of the role of parents, especiallymothers in educating children and this should be one of the important considerationsin fostering a bright future family. But what happens is just the opposite, where withthe growing number of children, the easier it is for parents to hand over theireducation and care to other parties or people, including formal education institutions.This study uses qualitative methods through related literature review. The results ofthis study revealed the importance of the government playing a role in educationthrough special attention to the existence of formal and non-formal educationinstitutions. In addition, government care is also important in improving the quality ofeducation for mothers as informal education providers for children. Though as amother who has a big role in parenting and children's education plays a veryimportant role so that the influence of the planting of children's intelligence should berealized by the mother. In order to be able to compete with other countries in thefuture, then a great attention to efforts to empower children needs to be improved.The government through institutions such as the Minister of National Education, theMinister of Women Empowerment, Minister of Health, BKKBN and others canbecome pioneers through related policies. Of course the Government must strive sothat the interest is accompanied by providing sufficient knowledge to the mothers. Therole of parents in the context of education also needs to be realized and improved inthe future.Kata kunci: Childcare, Education, Government Role